Neo-Carbon Core Concepts in Exploring Transformative Energy Futures 2050 - Sirkka Heinonen; Joni Karjalainen; Juho Ruotsalainen; Marjukka Parkkinen (Finland Futures Research Centre, University of Turku, 2022)
PREFACE
Neo-Carbon Energy is one of the strategic research openings of Tekes – the Finnish Funding Agency for Innovation. It is conducted by Technical Research Centre of Finland VTT Ltd, Lappeenranta University of Technology (LUT) and Finland Futures Research Centre (FFRC) at the University of Turku.
Neo-carbon energy entails a completely new energy system, where the produced energy is emission-free, cost-effective and independent. Energy is produced peer-to-peer in a distributed energy system of solar, wind, smart electricity grid, energy storages, and novel industrial uses based on renewable energy through neo-carbonization. As a whole, this will revolutionise the entire energy field.
The transformation of society takes place through socio-technological transitions. This signifies shifts in conceptual thinking, lifestyles and values, that are manifested in policies, and are further enabled by economic resources and novel innovations. New opportunities are often built and recognised, when existing patterns of behaviour, structures and concepts through which the world is seen are re-thought.
We see it worthwhile to identify key concepts that can be vehicles towards transformative energy futures. A limited number of concepts have been chosen according to their relevance to the Neo-Carbon Energy project. Some of the concepts presented in this paper are a reflection of emerging issues, while others are already well-established. All these concepts are reflected as regards their relevance to the project.
This working paper of Neo-Carbon core concepts was complied by the FFRC foresight research team of the project. Merja Lang, intern at the FFRC Helsinki office for summer 2016, also contributed to the writing process. The contents of this working paper will be modified during the research process.
Research group of WP1 of the NEO-CARBON ENERGY Project Helsinki 22nd December 2015